2019
DOI: 10.6000/1929-7092.2019.08.61
|View full text |Cite
|
Sign up to set email alerts
|

The Short and Long-Run Performance of Sharia-Compliant Initial Public Offerings (IPOs) in the Emerging Market: Evidence from the Saudi Arabia Share Market

Abstract: This study examines the short-and long-run share performance of 40 Sharia-compliant IPO companies listed on the Saudi Arabia Stock Exchange (Tadawul) from 1 st January 2000 to 31 st August 2017. This study employs both market-adjusted initial returns and buy-and-hold abnormal return to measure the share performance of IPOs. First, the analysis shows that Sharia-compliant IPOs are underpricing with abnormal initial returns of 79.23%. Second, the results suggest that investors could earn positive and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…For example, Alanazi and Al-Zoubi (2015) find that Saudi Arabian IPO firms underperform the Saudi Arabian all shares index, Tadawul, by 8.92%, in a one-year window. In contrast, Kamaludin and Zakaria (2018) find IPO firms listed in Saudi Arabia outperform Tadawul by 22% in a 12-month period. To date and to the best of our knowledge, there is no single empirical evidence that has yet examined the concurrent effects of mandatory IFRS and intertemporal changes in the quality of formal institutions on the aftermarket performance of IPO firms in emerging countries like Saudi Arabia.…”
Section: Brief Literature Reviewmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, Alanazi and Al-Zoubi (2015) find that Saudi Arabian IPO firms underperform the Saudi Arabian all shares index, Tadawul, by 8.92%, in a one-year window. In contrast, Kamaludin and Zakaria (2018) find IPO firms listed in Saudi Arabia outperform Tadawul by 22% in a 12-month period. To date and to the best of our knowledge, there is no single empirical evidence that has yet examined the concurrent effects of mandatory IFRS and intertemporal changes in the quality of formal institutions on the aftermarket performance of IPO firms in emerging countries like Saudi Arabia.…”
Section: Brief Literature Reviewmentioning
confidence: 76%
“…Note 33. Disclosure and IPO literature provide no consensus concerning the ideal length of time to proxy for long-term performance, as it ranges from a few weeks up to three years (Dorsman et al 2010;Alanazi & Al-Zoubi 2015;Kamaludin & Zakaria 2018). Due to the use of different time-windows to capture the aftermarket performance of IPO firms, this literature produces widely fragmented results.…”
Section: Od=ajperesandconvert_to=urlandcacheid=f9c937c6-6bef-46bb-8a91-9fmentioning
confidence: 99%
“…In comparison, AlShiab (2018) presented evidence that IPO businesses traded in Saudi Arabia beat the Tadawul by about 22.5 % over the course of one year. Likewise, Kamaludin and Zakaria (2018) found IPOs outperform by 9% over one year period.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Huang et al (2019), studied how IPO performance post listing depends on the stability and development of the financial market because of a better long-term positive outlook and lesser asymmetry of information. In this context, Kamaludin and Zakaria (2019) conducted a study on Sharia-Compliant IPOs on a short term and long term basis using market adjusted returns and abnormal return. The study observed that IPOs outperform the benchmark indices (equal weight and value weight) on a long run.…”
Section: Related Workmentioning
confidence: 99%